The Exact Absorbing Conditions Method in the Analysis of Open Electrodynamic Structures: Circular and Coaxial Waveguides - Seil S. Sautbekov; Yuriy K. Sirenko; Lyudmyla G. Velychko; Alexey A. Vertiy (International Journal of Antennas and Propagation)
The exact absorbing conditions (EAC) have been constructed and used for truncating an unbounded domain of computation in open initial boundary value problems, which describe space-time transformations of electromagnetic waves in axially symmetrical waveguides. The equivalence theorem is proved that gives grounds for rigorous theoretical justification of the EAC-method.